Ionosphere data assimilation modeling of 2015 St. Patrick's Day geomagnetic storm. Issue 11 (28th November 2016) - Chen, C. H.; Lin, C. H.; Matsuo, T.; Chen, W. H.
Abstract: The ionospheric plasma disturbances during a severe storm can affect human activities and systems, such as navigation and HF communication systems. Therefore, the forecast of ionospheric electron density is becoming an important topic recently. This study is conducted with the ionospheric assimilation model by assimilating the total electron content observations into the thermosphere‐ionosphere coupling model with different high‐latitude ionospheric convection models, Heelis and Weimer, and further to forecast the variations of ionospheric electron density during the 2015 St. Patrick's Day geomagnetic storm. The forecast capabilities of these two assimilation models are evaluated by the root‐mean‐square error values in different regions to discuss its latitudinal effects. Results show the better forecast in the electron density at the low‐latitude region during the storm main phase and the recovery phase. The well reproduced eastward electric field at the low‐latitude region by the assimilation model reveals that the electric fields may be an important factor to have the contributions on the accuracy of ionospheric forecast. Key Points: First time to assimilate the GPSTEC observations with different high‐latitude convection models in the TIEGCM Results show the latitudinal effect on the regional RMSEs and the capability of TEC forecast time The ionospheric assimilation system improves the storm time eastward electric fields